THE USEFUL WORDS WE NEED IN ENGLISH - Каландарова, Дилноза (Центр Научных Публикаций (buxdu.uz), 2021)
have you ever found yourself struggling to find the perfect word? You have an experience that feels so…so…but no words exist. You want to insult someone but can’t find a word vicious enough. You want to speak words of tender affection to your partner but no such words exist in the English language. Thankfully, there are other languages we can turn to in our time of need. Here are amazing foreign words that don’t exist in English. Use these words when English fails you. We’re going to start with our favorite Spanish words and then move onto other countries